Adipose Tissue Derivatives in Peripheral Nerve Regeneration after Transection: A Systematic Review - Araújo, Rafael Silva de; Mussalem, Matheus Galvão Valadares Bertolini; Carrijo, Gabriel Sant’Ana; Bani, João Victor de Figueiredo; Ferreira, Lydia Masako (Bioengineering (Basel), 2024)
Introduction: Peripheral nerve injury (PNI) is increasingly prevalent and challenging to treat despite advances in microsurgical techniques. In this context, adipose tissue derivatives, such as adipose-derived stem cells, nanofat, and stromal vascular fraction have been gaining attention as potential allies in peripheral nerve regeneration. Objectives: This study aims to explore the use of adipose tissue derivatives in nerve regeneration following peripheral nerve transection in murine models. Thus, we assess and synthesize the key techniques and methods used for evaluating the obtained nerve regeneration to guide future experimental research and clinical interventions. Methodology: A systematic review was conducted in February 2024, adhering to the Cochrane and PRISMA 2020 guidelines, using the PubMed, SciELO, and LILACS databases. The focus was on experimental studies involving adipose tissue derivatives in nerve regeneration in animal models post-transection. Only experimental trials reporting nerve regeneration outcomes were included; studies lacking a comparator group or evaluation methods were excluded. Results: Out of 273 studies initially identified from MEDLINE, 19 were selected for detailed analysis. The average study included 32.5 subjects, with about 10.2 subjects per intervention subgroup. The predominant model was the sciatic nerve injury with a 10 mm gap. The most common intervention involved unprocessed adipose-derived stem cells, utilized in 14 articles. Conclusions: This review underscores the significant potential of current methodologies in peripheral nerve regeneration, particularly highlighting the use of murine models and thorough evaluation techniques.